2008
DOI: 10.1038/bmt.2008.69
|View full text |Cite
|
Sign up to set email alerts
|

28 years of high-dose therapy and SCT for neuroblastoma in Europe: lessons from more than 4000 procedures

Abstract: Between 1978 and 2006, the European Group for Blood and Marrow Transplantation registered 4098 high-dose therapy (HDT) procedures followed by stem cell rescue (SCR) (3974 autologous/124 allogeneic) in patients with neuroblastoma. The 5-year rates for overall (OS) and event-free survival are 37 and 32%, respectively. The median age at diagnosis is 3.9 years (0.3-62 years) with 76 patients older than 18 years. Patients above 10 years carry a 2.5-fold higher risk. Younger patients cure significantly (o0.001) bett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(60 citation statements)
references
References 58 publications
3
53
0
4
Order By: Relevance
“…Modern, cisplatin-based chemotherapy provided for relatively poor long-term survival in neuroblastoma, 58 but this result was improved significantly with the addition of a single high-dose of melphalan and HCT. 59 Attempts to intensify the melphalan were associated with what was a high TRM, when this was a 'kill or cure' strategy (Lodenstein et al 60 Figure 1), but a subsequent randomised controlled trial confirmed the value of a melphalan-based combination including TBI, when compared to three courses of intensive multiagent chemotherapy. 61 This study also confirmed the benefit of the randomised addition of retinoid therapy post transplant, confirmed with much longer follow-up.…”
Section: Building On a Platform Of High-dose Melphalanmentioning
confidence: 99%
See 2 more Smart Citations
“…Modern, cisplatin-based chemotherapy provided for relatively poor long-term survival in neuroblastoma, 58 but this result was improved significantly with the addition of a single high-dose of melphalan and HCT. 59 Attempts to intensify the melphalan were associated with what was a high TRM, when this was a 'kill or cure' strategy (Lodenstein et al 60 Figure 1), but a subsequent randomised controlled trial confirmed the value of a melphalan-based combination including TBI, when compared to three courses of intensive multiagent chemotherapy. 61 This study also confirmed the benefit of the randomised addition of retinoid therapy post transplant, confirmed with much longer follow-up.…”
Section: Building On a Platform Of High-dose Melphalanmentioning
confidence: 99%
“…63 Figure 1. 100-day TRM and year of high-dose procedure for neuroblastoma (with permission, from Ladenstein et al 60 ).…”
Section: Building On a Platform Of High-dose Melphalanmentioning
confidence: 99%
See 1 more Smart Citation
“…The European Group for Blood and Marrow Transplantation data have shown that transplantation prolongs the course in pediatric cases of neuroblastoma and Ewing tumor (24,58,59). In other solid tumors, the patients may benefit from autologous transplantation in presence of the following special conditions (24): …”
Section: Solid Tumorsmentioning
confidence: 99%
“…The platelet engraftment is described as the platelet count of 20 x 10 9 / L and above without the support at least for 7 consecutive days. [1][2][3][4] Hemoglobin (Hb) level of more than 8 g / dl without support is regarded as the threshold for red cell engraftment. Graft failure is defined as no evidence of hematopoietic cell engraftment or hematologic recovery following an allo-HSCT.…”
Section: Graft Failurementioning
confidence: 99%